2017
DOI: 10.4172/2329-8901.1000159
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Lactobacillus Species Strengthen Intestinal Barrier Function and Tight Junction Integrity in Experimental Necrotizing Enterocolitis

Abstract: Necrotizing enterocolitis (NEC) is a serious intestinal disease that occurs in newborn infants. It is associated with major morbidity and affects 5% of all infants admitted to neonatal intensive care units. Probiotics have variable efficacy in preventing necrotizing enterocolitis. Tight junctions (TJ) are protein complexes that maintain epithelial barrier integrity. We hypothesized that the probiotics Lactobacillus rhamnosus and Lactobacillus plantarum strengthen intestinal barrier function, promote TJ integri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(98 citation statements)
references
References 45 publications
4
84
0
1
Order By: Relevance
“…Alternatively, the observed increase in Lactobacillus abundance may have resulted from the proliferation of the administered probiotic strain ( Takahashi et al, 2007 ). Certain lactobacilli, such as L. rhamnosus , L. reuteri , and L. plantarum , protect TJ proteins after stress and infection and may, therefore, contribute to TJ integrity and intestinal barrier function ( Yang et al, 2015 ; Blackwood et al, 2017 ). Further studies are needed to investigate specific species and their effects on piglet epithelial TJ proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the observed increase in Lactobacillus abundance may have resulted from the proliferation of the administered probiotic strain ( Takahashi et al, 2007 ). Certain lactobacilli, such as L. rhamnosus , L. reuteri , and L. plantarum , protect TJ proteins after stress and infection and may, therefore, contribute to TJ integrity and intestinal barrier function ( Yang et al, 2015 ; Blackwood et al, 2017 ). Further studies are needed to investigate specific species and their effects on piglet epithelial TJ proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Powdered SPI (ProFam 646, Archer Daniels Midland Company, Chicago, IL, USA) and Powdered WPI (ISOPURE, The Isopure company, Downers Grove, IL, USA) were dissolved in reverse osmosis water to yield 9% suspensions that were stored at 4 • C for 24 h prior to any UHPH or culture suspension in order to ensure full hydration of the powders and provide a sufficiently low inlet temperature during processing. A pure culture sample of Lactobacillus plantarum, (NRRL B-1927 aka ATCC 10241) originally isolated from sauerkraut and frequently identified as a probiotic [19][20][21], was obtained from the USDA-ARS Culture collection (Peoria, IL, USA) and used to propagate all cultures used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Probiotics are live microorganisms that, when ingested in adequate amounts, provide health benefits to the host. More recently, studies have shown that some beneficial effects of probiotic application include regulation of gut microbiota [8], enhancement of the mucosal barrier [9], stimulation of the immune system [10], and protection of epithelia [11]. Our team has previously shown that Bacillus amyloliquefaciens SC06 (Ba) is beneficial to intestinal tract of piglets, which also has a great antioxidant effect on IPEC-1 cells by regulating the Nrf2/Keap1 pathway [12,13], but effects of oxidative stress on intestinal structure and absorptive function were not completely understood.…”
Section: Introductionmentioning
confidence: 99%